LEVEL OF SELF-RESPECT AND ASSERTIVENESS SKILLS AND TEACHERS' EDUCATIONAL COMPETENCES - Anna Romanowska-Tolloczko; Agata Nowak; Jolanta Gnitecka (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: determining of self-respect level and assertiveness of teachers. Verification of whether there is a relationship between the measured trait and the correlation of educational competence. Material and methods: the study used three tools: Polish adaptation of SES M.Rosenberg's Self Esteem Scale, a questionnaire to determine the levels of assertiveness - P.Majewicz's Scale "I and others" and a questionnaire to examine the professional competence of teachers by A.Romanowska-Tołłoczko. The study examined 275 primary school teachers of different subjects. Results: after the statement of the research's results in the field of self-respect and assertiveness, it turns out that there is some regularity in relation to the level of the studied traits. People with high self-respect also receive higher scores assertive skills compared with those of average and low self-respect. This pattern is seen in all groups of teachers. Conclusions: although the observed differences are not great and statistically significant, they show some evidence of the occurrence trend of interdependence in a range of predispositions. Moreover, a positive correlation between the level of self-respect and assertiveness and parental perception of their competence was noted.